STUDI ETNOBOTANI TERHADAP PENGETAHUAN DAN PEMANFAATAN TUMBUHAN OBAT TRADISIONAL MASYARAKAT KELURAHAN AWANG TANGKA, KECAMATAN KAJUARA, KABUPATEN BONE - Restu Fadilah; Hafsah; Nurlaeliana (Universitas Cokroaminoto Palopo, 2025)
This ethnobotanical study investigates traditional medicinal plant knowledge and practices in Awang Tangka Village, Kajuara Subdistrict, Bone Regency. Using qualitative methods, data were collected through interviews, observations, and documentation from 29 participants comprising local residents, community leaders, and traditional healers (tabib). The study documented 34 plant species from 22 families used for medicinal purposes. Leaves were the most utilized plant part, followed by fruits, stems, rhizomes, flowers, bark, sap, and gel. Plants were sourced through cultivation, wild collection, or market purchase, and processed via boiling, pounding, extraction, or direct application. Findings demonstrate that ethnobotanical knowledge in Awang Tangka persists and transfers intergenerationally despite modern medicine's growing influence. This research provides scientific documentation, educational resources for biology teaching, and a basis for preserving indigenous knowledge and conserving medicinal plant biodiversity. Keywords: Ethnobotany, traditional medicine, medicinal plants, indigenous knowledge, Bone Regency